Prevalence of fetal alcohol spectrum disorder in Greater Manchester, UK: An active case ascertainment study. (29th September 2021) - McCarthy, Robyn; Mukherjee, Raja A. S.; Fleming, Kate M.; Green, Jonathan; Clayton‐Smith, Jill; Price, Alan D.; Allely, Clare S.; Cook, Penny A.
Abstract: Background: Despite high levels of prenatal alcohol exposure in the UK, evidence on the prevalence of fetal alcohol spectrum disorders (FASD) is lacking. This paper reports on FASD prevalence in a small sample of children in primary school. Methods: A 2‐phase active case ascertainment study was conducted in 3 mainstream primary schools in Greater Manchester, UK. Schools were located in areas that ranged from relatively deprived to relatively affluent. Initial screening of children aged 8–9 years used prespecified criteria for elevated FASD risk (small for age; special educational needs; currently/previously in care; significant social/emotional/mental health symptoms). Screen‐positive children were invited for detailed ascertainment of FASD using gold standard measures that included medical history, facial dysmorphology, neurological impairment, executive function, and behavioral difficulties. Results: Of 220 eligible children, 50 (23%) screened positive and 12% (26/220) proceeded to Phase 2 assessment. Twenty had a developmental disorder, of whom 4 had FASD and 4 were assessed as possible FASD. The crude prevalence rate of FASD in these schools was 1.8% (95% CI: 1.0%, 3.4%) and when including possible cases was 3.6% (2.1%, 6.3%). None of these children had previously been identified with a developmental diagnosis. Conclusions: FASD was found to be common in these schools and most of these children's needs had not previously been identified. A larger, more definitive study that uses a random sampling technique stratified by deprivation level to select schools is needed to make inferences regarding the population prevalence of FASD. Abstract : A two‐phase active case ascertainment study in mainstream primary schools in the UK where 220 children aged 8‐9 years were screened for elevated FASD risk and screen positive children were invited for detailed ascertainment of FASD using gold standard measures. The crude prevalence rate of FASD was 1.8% (95%CI: 1.0%, 3.4%). The rate was 3.6% (2.1%, 6.3%), if any possible cases were included. FASD was found to be common in these schools, but limitations to the sampling restrict inferences to a population prevalence.